Dissection of metabolic reprogramming in polycystic kidney disease reveals coordinated rewiring of bioenergetic pathways. (December 2018) - Podrini, Christine; Rowe, Isaline; Pagliarini, Roberto; Costa, Ana; Chiaravalli, Marco; Di Meo, Ivano; Kim, Hyunho; Distefano, Gianfranco; Tiranti, Valeria; Qian, Feng; di Bernardo, Diego; Frezza, Christian; et al.
Abstract Autosomal Dominant Polycystic Kidney Disease (ADPKD) is a genetic disorder caused by loss-of-function mutations inPKD1 orPKD2 . Increased glycolysis is a prominent feature of the disease, but how it impacts on other metabolic pathways is unknown. Here, we present an analysis of mousePkd1 mutant cells and kidneys to investigate the metabolic reprogramming of this pathology. We show that loss ofPkd1 leads to profound metabolic changes that affect glycolysis, mitochondrial metabolism, and fatty acid synthesis (FAS). We find thatPkd1 -mutant cells preferentially use glutamine to fuel the TCA cycle and to sustain FAS. Interfering with either glutamine uptake or FAS retards cell growth and survival. We also find that glutamine is diverted to asparagine via asparagine synthetase (ASNS). Transcriptional profiling ofPKD1 -mutant human kidneys confirmed these alterations. We find that silencing ofAsns is lethal inPkd1 -mutant cells when combined with glucose deprivation, suggesting therapeutic approaches for ADPKD. Christine Podrini et al. present a comprehensive analysis ofPkd1 mutant mouse cells and kidneys, providing new insight into autosomal dominant polycystic kidney disease (ADPKD). They find thatPkd1 loss leads to profound metabolic changes, including asparagine synthase-driven glutamine anaplerosis.